Housing precariousness and health: a mixed-methods study into households affected by displacements and demolitions in East Jerusalem. (June 2022) - Bouquet, Ben; Massalha, Manal; Nassar, Juliana; al-Natsheh, Bashaer; Giacaman, Rita
Abstract: Background: East Jerusalem residency status for more than 350 000 Palestinians depends on showing that there is a continued centre of life in the city and can be revoked on the grounds of a breach of allegiance. 2975 Palestinians in East Jerusalem were displaced or had their homes demolished between 2009 and 2021, primarily on the grounds of not having Israeli-issued building permits, which are highly difficult to obtain, or settler takeover. We aimed to explore the perceived health effects of demolition or displacement, and to assess self-reported health and the intersection of housing precariousness and other forms of precarity in East Jerusalem. Methods: We did a mixed-methods study in East Jerusalem. Drawing on a database of demolition or displacement in East Jerusalem from 2009 to 2019, we undertook ten household case studies, using in-depth interviews, site visits, and visual ethnography, and surveyed a systematic random sample of 120 women, each representing a separate household that underwent demolition or displacement during 2017–19. In the qualitative component, we chose a mix of different types of demolition or displacement and post-displacement housing trajectories. We used survey tools to assess household demographics; exposure to different forms of precarity and occupation-related violence; a measure of human insecurity (Birzeit University human insecurity scale); and self-reported health (SF-12 version 2 assessment), wellbeing (WHO-Five Wellbeing Index), and disability (Washington Group short questions). Findings: We examined the perceived health effects of demolition or displacement related to experiences of the event; subsequent housing quality; subsequent neighbourhood and its environmental quality; the under-provision of municipal services; and psychosocial stress connected with affordability, tenure, and absence of security and legal protections. The survey response rate was 84 households (70%) of 120. 79 households (94%) of 84 underwent demolition, whereas five households (6%) were displaced without demolition. 19 households (24%) of 79 experienced two or more incidences of demolition and six households (7%) of 84 had at least one family member who had lost East Jerusalem residency. Economically, in 22 households (26%), the head of the household was unemployed, 45 households (54%) worried daily about debt, and 32 households (38%) met the criteria for overcrowding (three or more people per room). From 18 households (21%), women reported experiencing personal humiliation by occupation forces, whereas women from 33 households (39%) reported exposure to acts of humiliation of others, and women from 18 households (21%) reported the detention or arrest of other household members. Women from 39 households (46%) experienced high human insecurity; the mean SF-12 version 2 assessment score was 46·6 (SD 22·1) for physical health and 43·4 (SD 18·3) for mental health, where a score of less than 50 would indicate a state of health worse than expected for the mean of the population; whereas the prevalence of poor wellbeing, according to the WHO wellbeing index, was 86% (72 households). Interpretation: Our study supports previous research on the damaging health effects of housing precariousness, shown by the poor self-reported health of the women surveyed and a high exposure to different forms of precarity. Israel's occupation policies in East Jerusalem result in insecure residency status and tenure for many households, neglect in the provision of health and public health services, overcrowding, and unsanitary housing and neighbourhood conditions that are hazardous to health. Funding: Swiss Development Cooperation.